Synthesis and characterization of divalent metal complexes with bipyridylamide ligands. Issue 3 (1st February 2016) - McMoran, Ethan P.; Mugenzi, Clement; Fournier, Kyle; Draganjac, Mark; Tony, Donavon; Jeong, Kwangkook; Powell, Douglas R.; Yang, Lei
Abstract: Reaction of N -(4-pyridyl)picolinamide (4-ppa), N -(4-pyridyl)nicotinamide (4-pna), N -(4-pyridyl)isonicotinamide (4-pina), and N -(2-pyridyl)isonicotinamide (2-pina) with divalent metal salts led to the formation of six new coordination complexes. The X-ray structure of [Zn(4-ppa)2 Cl2 ] (1 ) shows a mononuclear structure with interesting intermolecular hydrogen bonding interactions. [Zn(4-pna)(OAc)2 ]n (2 ), Cu(4-pna)(OTf)2 (DMF)2 ]n (3 ), {[Zn(4-pina)(DMF)4 ](OTf)2 }n (4 ), {[Fe(4-pina)(DMF)4 ](OTf)2 }n (5 ), and [Cu(2-pina)(OTf)2 (DMF)2 ]n (6 ) are one-dimensional coordination polymers with conformational differences caused by the coordination donor disposition, which demonstrates the flexibility of the pyridylamide ligands in polymeric structures. Reflectance UV-visible spectra and thermal properties of the coordination polymers are also reported. Abstract :